2012
DOI: 10.7205/milmed-d-11-00133
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Examination of Risk-Taking Behavior and PTSD Symptom Severity in a Veteran Sample

Abstract: The present study conducted an exploratory examination of the relationship between self-reported symptoms of post-traumatic stress disorder and an expanded definition of risk-taking behaviors among 395 veterans at a large Midwestern Veterans Affairs Medical Center. Post-traumatic stress disorder symptoms were associated with elevated rates of substance use, thrill seeking, aggression, risky sexual practices, and firearm possession. Results indicated that suicidal ideation and aggressive driving behavior were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 35 publications
5
58
0
Order By: Relevance
“…With respect to drinking and driving, the rates found via traditional anonymous assessment in our sample approximate those found by Kuhn et al 12 and Strom et al 13 whereas the rates revealed by the UCT were nearly 50% higher. Given the high-risk nature of carrying firearms and driving under the influence, it was concerning to find that these were the two of the most common risky behaviours in this sample.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…With respect to drinking and driving, the rates found via traditional anonymous assessment in our sample approximate those found by Kuhn et al 12 and Strom et al 13 whereas the rates revealed by the UCT were nearly 50% higher. Given the high-risk nature of carrying firearms and driving under the influence, it was concerning to find that these were the two of the most common risky behaviours in this sample.…”
Section: Discussionsupporting
confidence: 81%
“…Sayer et al 4 assessed risky driving with a single item and found that 35% of a sample of OEF/OIF veterans receiving treatment at a Veterans Affairs facility had learned from someone else that they drove dangerously. Strom et al 13 assessed rates of several types of risky driving as part of a broader study of risk-taking behaviour in treatment-seeking OEF/OIF veterans; they found rates of risky driving that ranged from 14.8% to 72.2%. The handful of studies conducted to date yield a wide range of base rate estimates on a variety of risky driving behaviours 4 6 12 13…”
mentioning
confidence: 99%
“…PTSD as a consequence of combat-related trauma demonstrates particularly robust associations with anger difficulties and overt aggression (Beckham, Moore, & Reynolds, 2000; Orth & Wieland, 2006). Although anger symptoms continue to be influential in the maintenance of PTSD subsequent to MVA (e.g., Mayou, Ehlers, & Bryant, 2002), examination of anxiety-based driving aggression within veterans samples may be warranted, particularly given known difficulties with traffic-related cues in this population (e.g., Kuhn, Drescher, Ruzek, & Rosen, 2010; Sayer et al, 2010; Strom et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Individuals with trauma exposure and higher PTSD symptom severity demonstrate elevated levels of impulsivity and risk-taking, as indexed by a variety of behavioral and self-report measures (Casada & Roache, 2005;Chamorro et al, 2012;Killgore et al, 2008;Lovallo, 2013;Strom et al, 2012;Weiss, Tull, Anestis, & Gratz, 2013). Given the associations between PTSD and impulsivity, and between impulsivity and aggressive behavior, it is plausible that impulsivity mediates the impact of PTSD symptoms on aggressive behavior among individuals with SUD.…”
Section: Impulsivitymentioning
confidence: 98%